Manual therapeutic plasma exchange for treatment of a dog with suspected acute canine polyradiculoneuritis - Czerwik, Adriana; Jarešová, Tereza; Olszewska, Agnieszka; Farke, Daniela; Schmidt, Martin Jürgen; Lehmann, Hendrik; Justus Liebig University Giessen (My University, 2023)
Background: Acute canine polyradiculoneuritis is one of the most common polyneuropathies occurring in dogs. The disease is very similar to the Guillain–Barré syndrome in humans. In veterinary medicine, there is no established treatment for this disease, while in human medicine, therapeutic plasma exchange and intravenous immunoglobulin administration are two main immunotherapy treatments of this syndrome. Case presentation: A 12-year-old male Jack Russel Terrier was presented with a history of acute weakness of the pelvic limbs progressing to flaccid tetraplegia with respiratory compromise. Complete diagnostic workup was performed including blood work, diagnostic imaging (radiographs of the thorax as well as ultrasound of the abdomen) and echocardiography. Based on the clinical course, neurological localisation and the results of electrodiagnostic examination acute canine polyradiculoneuritis was suspected. During the hospitalization, the dog deteriorated and was admitted to the intensive care unit for respiratory support via tracheostomy tube. In addition to symptomatic treatment, immunotherapy via single treatment of manual therapeutic plasma exchange was administered. This procedure was safe, and the dog showed improvement of clinical signs 3 days after therapy was initiated, as well as improvement of neurological signs (from grade 4 tetraplegia to grade 3) within 5 days. However, the dog was euthanized 3 weeks later due to complications related to the tracheostomy. Conclusions: This is the first case report of a manual therapeutic plasma exchange in a dog with suspected acute canine polyradiculoneuritis suggesting that this method is safe and well tolerated in dogs with this disease. It may be a reasonable adjunctive treatment to supportive therapy in severe cases.
Keywords: Canine; Guillain-Barré syndrome; Neuromuscular disease; Therapeutic plasma exchange; ddc:630